Analytical methods. Zircon and monazite geochronology of deformation in the Pielavesi Shear Zone, Finland: multistage evolution of the Archaean–Proterozoic boundary in the Fennoscandian Shield - Jeremy Woodard; Pekka Tuisku; Aulis Kärki; Yann Lahaye; Jarosław Majka; Hannu Huhma; Martin J. Whitehouse (2016)
Analytical Methods